Understanding African music -- Listen and learn: music made easy -- For future generations: Hugh Tracey and the International Library of African Music -- Sound of Africa -- Music of Africa -- Historical recordings by Hugh Tracey -- Soul safari series -- The Dhow Countries Music Academy: Zanzibar (International Library of African Music, 2016)
pages: 232-239
Keywords: African Music